2005
DOI: 10.1186/1742-4755-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality in the rural Gambia, a qualitative study on access to emergency obstetric care

Abstract: BACKGROUND: Maternal mortality is the vital indicator with the greatest disparity between developed and developing countries. The challenging nature of measuring maternal mortality has made it necessary to perform an action-oriented means of gathering information on where, how and why deaths are occurring; what kinds of action are needed and have been taken. A maternal death review is an in-depth investigation of the causes and circumstances surrounding maternal deaths. The objectives of the present study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
158
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(191 citation statements)
references
References 23 publications
26
158
2
5
Order By: Relevance
“…Lack of awareness of danger signs in pregnancy was a crucial factor. This finding is consistent with other studies about lack of awareness of pregnancy danger signs [19,20]. Socioeconomic status, extended family size, health beliefs, access and level of trust in available local medical care may have affected the decision to seek care.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Lack of awareness of danger signs in pregnancy was a crucial factor. This finding is consistent with other studies about lack of awareness of pregnancy danger signs [19,20]. Socioeconomic status, extended family size, health beliefs, access and level of trust in available local medical care may have affected the decision to seek care.…”
Section: Discussionsupporting
confidence: 82%
“…Socioeconomic status, extended family size, health beliefs, access and level of trust in available local medical care may have affected the decision to seek care. Other studies had reported the notion that different cultures affect women's care-seeking decisions, despite the existence of similar danger signs [14,[19][20][21]. In addition, religious beliefs may have affected the decision of those women who refused pregnancy termination.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly a study aimed to describe the socio-cultural and health service factors associated with maternal death in rural Gambia showed that women reached the health facilities on time to seek emergency obstetric care, but lack of collaboration between physicians and midwives contributed to the disorganized and delayed health care to respond to obstetric emergencies. [35] Our study findings related to inter-professional collaboration between midwives and physicians concur with previous study results examining the collaboration between midwives, nurses and physicians in maternity services. [36,37] Simpson et al [38] found that nurse-midwives and physicians in maternity services had a common objective of improving maternal and neonatal outcomes; however, they did not always come to an understanding on how to achieve that shared objective.…”
Section: Discussionsupporting
confidence: 82%
“…In their survey PRRINN-MNCH (2010) reported respondents as having to pay so much for a unit of blood, this finding was similar to that of other studies [8]. In addition, blood banking systems in most centres are not very efficient [9], and in most instances patients' relations have to look for donors themselves; this could be from among family members or from friends and well-wishers. In other studies patients' relations have had to travel several kilometres away from a health facility in search for a compatible donor because of the inefficiency of the blood banking system in their own health facility [10].…”
Section: Discussionsupporting
confidence: 74%